2018
DOI: 10.3390/pharmaceutics10030138
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the CD81 Large Extracellular Loop with De Novo Disulfide Bonds Improves Its Amenability for Peptide Grafting

Abstract: Tetraspan proteins are significantly enriched in the membranes of exosomal vesicles (EVs) and their extracellular domains are attractive targets for engineering towards specific antigen recognition units. To enhance the tolerance of a tetraspanin fold to modification, we achieved significant thermal stabilization of the human CD81 large extracellular loop (hCD81 LEL) via de novo disulfide bonds. The best mutants were shown to exhibit a positive shift in the melting temperature (Tm) of up to 25 °C. The combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Surprisingly, of the 18 mutants proposed by the algorithm, only eight could be expressed, and only one mutant with novel disulfide bonds in both α‐ and β‐chains was stabilized. The success of prediction was lower than achieved with DSDBASE algorithm with other proteins, such as the Fc fragment or the large extracellular loop of CD81, an α‐helical protein of the tetraspanin family . One reason might be that the chosen algorithm mainly takes into account the parameters of secondary structure provided, and the regions of TCR where the proposed stabilization mutations cluster can be less prominently assigned to such particular elements.…”
Section: Discussionmentioning
confidence: 94%
“…Surprisingly, of the 18 mutants proposed by the algorithm, only eight could be expressed, and only one mutant with novel disulfide bonds in both α‐ and β‐chains was stabilized. The success of prediction was lower than achieved with DSDBASE algorithm with other proteins, such as the Fc fragment or the large extracellular loop of CD81, an α‐helical protein of the tetraspanin family . One reason might be that the chosen algorithm mainly takes into account the parameters of secondary structure provided, and the regions of TCR where the proposed stabilization mutations cluster can be less prominently assigned to such particular elements.…”
Section: Discussionmentioning
confidence: 94%
“…Availability of several high‐resolution crystal structures has corroborated CD81 LEL as an independent folding unit (Cunha et al., 2018 ; Kitadokoro, 2001 ; Kitadokoro et al., 2001 ; Nelson et al., 2018 ). Previously, we have attempted to improve the biophysical properties of CD81 LEL and constructed mutants that exhibit in one case an extremely high level of thermostability and in one case reversible thermal denaturation (Vogt et al., 2018 ). As these should be more permissive for mutagenesis required to introduce a novel antigen binding site, we have identified amino acid residues that could form a novel antigen‐binding surface based on the above mutants.…”
Section: Resultsmentioning
confidence: 99%
“…The crystallographic structure of a soluble form of the tetraspanin CD81 LEL domain is a five‐helix bundle stabilized by two disulfide bridges (Kitadokoro, 2001 ; Kitadokoro et al., 2001 ). The protein fold as well as its key structural features are conserved among tetraspanins, while a high degree of variability in its length and composition can be found in its central part that in CD81 comprises three helices (Seigneuret, 2006 ; Seigneuret et al., 2001 ) Previously, we have designed highly stabilized mutants of CD81 LEL via introduction of de novo disulfide bonds (Vogt et al., 2018 ). Two such CD81 LEL variants, the most stable one and the variant that exhibited reversible refolding after denaturation, were chosen to serve as scaffolds for libraries of antigen‐binding units, obtained by randomization of selected solvent‐exposed residues.…”
Section: Introductionmentioning
confidence: 99%
“…Misfolded regions can be used to determine important interaction regions within a protein. For CD81, a member of the tetraspanin superfamily, it has been shown that cysteines within the LEL are important for stabilizing the protein folding 49 . The same observation was made with FRET experiments where the point mutations C145A and C146A led to a decrease in PPI strength (Fig.…”
Section: Discussionmentioning
confidence: 99%